MENINGKATKAN HASIL BELAJAR DAN AKTIVITAS SISWA DALAM PEMBELAJARAN IPA MELALUI MODEL PEMBELAJARAN BERBASIS PENEMUAN (DISCOVERY LEARNING) KELAS VI MADINAH SD NEGERI 002 KUOK - Asna, Asna (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
The purpose of this study was to improve learning outcomes, improve science learning activities for fourth grade students of Madina SD Negeri 002 Terpadu Kuok, Kuok District, Kampar Regency and to motivate teachers to develop learning models and strategies in the science learning process. The research model is Classroom Action Research. This study uses a Discovery Learning model. The application of Classroom Action Research has the objective of improving and or increasing science learning achievement. The results showed: (1) By using the Discovery Learning-based learning model in science learning, student learning outcomes in each cycle experienced significant changes. Student learning outcomes in cycle 1 an average of 71.60 with completeness 22.72% then increased in cycle 2 an average of 85.93 with completeness 95.45% with 21 students complete and 1 student who has not completed. Students who are active in learning reach 92%. After the implementation of the appropriate Discovery Learning-based learning model, the activities and achievements of science learning in Grade VI Madina SD Negeri 002 Integrated Kuok can increase.